Final-year university students’ mental health and access to support as they prepared to graduate - Megan J. Magier; Madelyn Law; Sarah Pennisi; Tanya Martini; Markus J Duncan; Hussain Chattha; Karen A Patte (Cogent Mental Health)
Previous research has examined postsecondary student mental health and transitions into university. However, research focused on the transition out of university is lacking. Challenges may be experienced differently among population subgroups. We examined the mental health and support access of university students approaching graduation and differences by various social positions. Survey data were collected from final-year undergraduate students that had registered to graduate at a Canadian university in 2021 and 2022. Chi-square and linear regression models analyzed relationships between sociodemographic characteristics and mental health outcomes. Open-ended questions assessed barriers to accessing support and desired supports. Sexual/gender diverse students reported greater depressive symptoms than cisgender heterosexual students. Students without stressful childhood or current financial situations had lower depression and anxiety scores than their peers that experienced stressful financial situations, respectively. Formal support was more commonly accessed off-campus than on-campus in the past year. Differences in past-year support access were found by gender/sexuality, financial stress, age and race/ethnicity. Availability/scheduling was the most reported barrier to accessing campus-based services. Financial concerns were a common challenge and area for desired support. Implementing developmentally specific mental health support catering to the demands of this life period is necessary.